Equalizing and Widening Access to Higher Education During a Pandemic : Lessons Learned from a Multi-University Perspective. - Dodd, Emlyn; Singh, Sonal; Micsko, Jim; Austin, Kylie; Morison, Carolina; Upton, Stuart (Student Success v.12 n.3 p.58-72 https://doi.org/10.5204/ssj.1715, 2021)
The COVID-19 pandemic caused a rapid and unprecedented shift of widening participation and outreach activities to online and remote delivery. The impact of this went beyond practitioners and the university sector; positive and negative implications are felt by stakeholders and the broader community. This shift online is discussed through the lens of a multi-university perspective, using four case studies from university outreach programs in one Australian state. The article provides a holistic view of the lessons learned and discoveries made, informing future program design and delivery. These programs include primary and secondary students, teachers, parents, guardians and carers, and work within a range of low socioeconomic and regional, rural and remote contexts. We argue that the fundamentally necessary shift online created a profound legacy and bears potential to increase accessibility (via diversity and scale), but, simultaneously, that care must be applied if substituting face-to-face engagement with that online. While this article primarily focuses on issues of value to practitioners, it also discusses important implications for academics, support staff, and university executive regarding the access and participation of underrepresented cohorts during times of mass change. [Author abstract]